2011
DOI: 10.1016/j.rse.2011.01.019
|View full text |Cite
|
Sign up to set email alerts
|

C-correction of optical satellite data over alpine vegetation areas: A comparison of sampling strategies for determining the empirical c-parameter

Abstract: Semi-empirical topographic normalization methods (e.g., C-correction) have been widely used to correct illumination differences in optical satellite data. The objective of this study was to examine the precision and accuracy of the C-correction's empirical parameter, c, as a function of the sample from which it was derived. Three sampling methods were compared: a random sample, a sample stratified on north and south aspects, and a sample stratified by cosine of the solar incidence angle, i. In the latter, powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 42 publications
3
45
0
2
Order By: Relevance
“…The dark object subtraction approach [45] was used to conduct atmospheric calibration so that the surface reflectance values ranged from 0 to 1. The ASTER GDEM data with spatial resolution of 30 mˆ30 m at the same coordinate system as the TM image were used to conduct topographic correction for the Landsat 5 TM image using the C-correction approach [46,60]. Table 4 provides the definitions of each vegetation type based in the forest inventory data.…”
Section: Collection Of Remote Sensing and Dem Data And Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark object subtraction approach [45] was used to conduct atmospheric calibration so that the surface reflectance values ranged from 0 to 1. The ASTER GDEM data with spatial resolution of 30 mˆ30 m at the same coordinate system as the TM image were used to conduct topographic correction for the Landsat 5 TM image using the C-correction approach [46,60]. Table 4 provides the definitions of each vegetation type based in the forest inventory data.…”
Section: Collection Of Remote Sensing and Dem Data And Preprocessingmentioning
confidence: 99%
“…Many factors influence the data saturation of Landsat imagery [5,6,[44][45][46][47][48]. The limitation of remote sensing data themselves in spectral, spatial, and radiometric resolutions may result in different saturation values of AGB.…”
Section: Introductionmentioning
confidence: 99%
“…C-correction is a semi-empirical topographic correction method, which consists of a modified cosine correction with the empirical parameter cλ (Reese & Olsson, 2011). cλ (Eq.…”
Section: Topographic Correction Of Landsat-datamentioning
confidence: 99%
“…Several studies have demonstrated the viability of C-correction for radiometric correction of multitemporal images taken under different illumination conditions (Moreira & Valeriano, 2014;Reese & Olsson, 2011;Vanonckelen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“… To reduce the topographic effect by topographic normalization techniques [1,[11][12][13][14][15][16][17][18][19][20][21];  As an additional -channel‖ increasing forest map accuracy [9,[22][23][24][25];  Combined with expert knowledge or a decision tree enhancing classification accuracy [26][27][28];  Integrating the prior probability of the relationship between elevation and vegetation distributions improving image classification [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%